Pendekatan Klinis Sindrom Takotsubo: Tinjauan Pustaka - Pramudya, Ricky (PT Kalbe Farma Tbk., 2026)
Takotsubo syndrome (TTS) or cardiomyopathy due to stress is defined as a syndrome of acute systolic and diastolic dysfunction of the left ventricle, usually associated with emotional or profound physical stress. The incidence of Takotsubo syndrome has increased dramatically during the COVID-19 pandemic, which is closely related to psychological stressors such as social isolation, financial problems, and anxiety. Increased sympathetic stimulation with massive catecholamine release plays a major role in the pathogenesis of Takotsubo cardiomyopathy. An accurate history of the emotional and physical events preceding the onset of symptoms is the most important diagnostic tool. In the acute phase, most complaints are typical chest pain similar to myocardial infarction, while others come with symptoms of heart failure, such as dyspnea, orthopnea and/or acute pulmonary edema or syncope. An important clinical marker of Takotsubo cardiomyopathy is an increase in N-terminal prohormone of brain natriuretic peptide (NT proBNP), which has been shown to be directly related to elevated blood catecholamine concentrations, a marker of sympathetic overreaction, and the severity of left ventricular dysfunction with associated systemic complications, such as pulmonary edema. Supportive and symptomatic treatment should be provided in the acute phase. Patients with Takotsubo cardiomyopathy have a good prognosis, with left ventricular function recovering within days and fully recovering within 3–4 weeks.